Strengthening Writing Literacy Based on Local Culture Through the â€œDinoyo Ceramics and Iâ€ Strategy - Zahro’, Azizatuz; Sulistyorini, Dwi; @Mustaffa, Madiawati Mamat; Lestari, Nunik Martin; Mustayah, Mustayah; Jumain, Jumain (JOLLT Journal of Languages and Language Teaching, 2025)
Integrating writing instruction with local cultural elements is essential for improving literacy outcomes that resonate with students’ lived experiences and cultural identities. However, field observations reveal that such integration remains underutilized in many educational contexts, including at SD Negeri Dinoyo 2 Malang, East Javaâ€”a school situated in a region known for its ceramic industry. This classroom action research aimed to enhance students’ writing skills using the culturally rooted strategy titled "Dinoyo Ceramics and I." Conducted over two cycles with 25 students from Class 5A, the study began by introducing students to Dinoyo ceramic products through physical artifacts and visual media showcasing their historical significance. Students were then encouraged to describe these items in terms of their appeal, function, and value as souvenirs or treasured objects. Based on this exposure, students generated writing ideas under the theme "Dinoyo Ceramics and I," which they first organized into outlines and then developed into full compositions. In the second cycle, imaginative elements were incorporated to enrich the outlines, and students were guided to present each idea in a well-structured paragraph. This approach enabled students to creatively weave personal experiences into compelling narratives that retained Dinoyo ceramics as a central motif. The strategy sparked greater engagement, as students connected deeply with a topic rooted in their cultural environment. The findings highlight the importance of recognizing studentsâ€™ everyday experiences as meaningful content for writing. Thus, educators should consider incorporating local cultural themes into writing instruction to build more relevant, motivating, and expressive learning experiences.